Apatinib Suppresses Gastric Cancer Stem Cells Properties by Inhibiting the Sonic Hedgehog Pathway - Cao, Wanshuang; Li, Yuan; Sun, Hongliang; Yang, Chenying; Zhu, Jianyun; Xie, Chunfeng; Li, Xiaoting; Wu, Jieshu; Geng, Shanshan; Wang, Lu; Sun, Liangfei; Geng, Guozhu; et al. (Frontiers in Cell and Developmental Biology, 2021)
The presence of gastric cancer stem cells (GCSCs) marks the onset of gastric carcinoma. The sonic hedgehog (SHH) pathway plays a vital role in the maintenance of GCSC characteristics. Apatinib has been approved in China for advanced gastric cancer (GC) treatment. However, whether apatinib can target GCSCs and affect the SHH pathway remains unclear. The present study aimed to investigate the underlying mechanism of apatinib’s antitumor effects on GC. The expression levels of GCSC markers and number of CD133+ cells were significantly elevated in the sphere-forming cells. Apatinib effectively suppressed GCSC traits by inhibiting tumorsphere formation and cell proliferation, suppressing GCSC markers expression and CD133+ cell number, and inducing apoptosis. Apatinib downregulated the activation of the SHH pathway; while upregulation of the SHH pathway attenuated the inhibitory effects of apatinib on GCSCs. Moreover, apatinib treatment significantly delayed tumor growth and inhibited GCSC characteristics in the xenograft model. Our data suggested that apatinib exhibited inhibitory effects on GCSCs by suppressing SHH pathway both in vitro and in vivo, thus providing new insights into the therapeutic application of apatinib in GCSC suppression and advanced gastric cancer treatment.